Population, poverty, politics and the reproductive health bill - Ernesto M. Pernia; Stella Alabastro-Quimbo; Maria Joy V. Abrenica; Ruperto P. Alonzo; Agustin L. Arcenas; Arsenio M. Balisacan; Dante B. Canlas; Joseph J. Capuno; Ramon L. Clarete; Rolando A. Danao; Emmanuel S. de Dios; Aleli dela Paz-Kraft; et al. (University of the Philippines, School of Economics (UPSE), 2011)
Following an earlier paper titled 'Population and Poverty: The Real Score' (UPSE Discussion Paper 0415, December 2004), the present paper was first issued in August 2008 as a contribution to the public debate on the population issue that never seemed to die in this country. The debate heated up about that time in reaction to a revival of moves to push for legislation on reproductive health and family planning (RH/FP). Those attempts at legislation, however, failed in the 13th Congress, and again in the 14th Congress. Since late last year, the debate has been heating up further on the heels of President Noy Aquino's pronouncements seeming to favor RH/FP, though he prefers the nomenclature 'responsible parenthood'. With some updating of the data, this paper remains as relevant as ever to the ongoing public debate. It is being re-issued as a Discussion Paper for wider circulation.
Keywords: 330; Armut; Bevölkerungsentwicklung; Familienpolitik; Wirkungsanalyse; Philippinen